2016
DOI: 10.6002/ect.2015.0197
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: The optimal dose of rabbit antithymocyte globulin induction therapy in kidney transplant recipients with high immunologic risk lacks consensus. The purpose of this study was to evaluate the effect of using ideal body weight rather than total body weight for the weight-based dose calculations in this patient population. Materials and Methods: Data were retrospectively collected on 89 adult patients who received rabbit antithymocyte globulin induction therapy for high immunologic risk kidney transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Unfortunately, patients were not actually dosed based on IBW and exact cumulative dose exposure was not reported. 10 Another publication compared rATG >7.5 mg/kg IBW to <7.5 mg/kg IBW, finding no difference in biopsyproven rejection rates or graft survival. This investigation was limited by its small sample size and failure to report total dose received, limiting comparability to contemporary dosing strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, patients were not actually dosed based on IBW and exact cumulative dose exposure was not reported. 10 Another publication compared rATG >7.5 mg/kg IBW to <7.5 mg/kg IBW, finding no difference in biopsyproven rejection rates or graft survival. This investigation was limited by its small sample size and failure to report total dose received, limiting comparability to contemporary dosing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This approach may be particularly sensible in the setting of increasing rates of obesity in the transplant population. 10 Two studies have found these strategies to yield favorable outcomes related to rejection and graft function; however they are limited by small sample sizes and lack of specific information about cumulative dose exposure. 10,11 This quality improvement study sought to evaluate posttransplant care process improvement through dose minimization of rATG using an IBW-based dosing protocol in a large cohort of kidney transplant recipients.…”
mentioning
confidence: 99%